1986
DOI: 10.1161/01.cir.73.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of serum sodium concentration and its modification by converting-enzyme inhibition in patients with severe chronic heart failure.

Abstract: Although past reports have identified a variety of prognostic factors in patients with severe chronic heart failure, previous studies have not evaluated the interaction of prognostic variables and drug treatment. We analyzed the association of 30 clinical, hemodynamic, and biochemical variables with survival in 203 consecutive patients with severe heart failure; all variables were assessed just before initiation of treatment with a variety of vasodilator drugs, and all patients were subsequently followed for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
227
4
10

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 532 publications
(249 citation statements)
references
References 60 publications
8
227
4
10
Order By: Relevance
“…Franciosa 62 found a higher mortality in patients with LV filling pressures higher than 27mmHg, systemic vascular resistance higher than 23 Wood units, and cardiac index smaller than 2.25L/min/m 2 . Some authors, however, found no significant correlation between LV filling pressures, cardiac output and mortality, even though these variables were slightly altered in those who did not survive 52,63 .…”
Section: Hemodynamic Variablesmentioning
confidence: 98%
See 4 more Smart Citations
“…Franciosa 62 found a higher mortality in patients with LV filling pressures higher than 27mmHg, systemic vascular resistance higher than 23 Wood units, and cardiac index smaller than 2.25L/min/m 2 . Some authors, however, found no significant correlation between LV filling pressures, cardiac output and mortality, even though these variables were slightly altered in those who did not survive 52,63 .…”
Section: Hemodynamic Variablesmentioning
confidence: 98%
“…In patients in advanced stages of CHF (FC III and IV and low EF), the hemodynamic and functional factors are no longer predictors of the disease course, and the factors related to the neurohormonal system are fundamental for determining prognosis 27,52,63,67 . Several systems are activated in CHF in order to compensate for the circu-latory disorder caused by reduction of the cardiac output.…”
Section: Neurohormonal Systemmentioning
confidence: 99%
See 3 more Smart Citations